2019
DOI: 10.21608/ejnf.2019.103446
|View full text |Cite
|
Sign up to set email alerts
|

Imroving Nutritive Value of Olive Trees by-Products by Biological and Chemical Treatmentsand Its Effect on Sheep Performance

Abstract: his experiment was conducted to study the effect of biological and chemical treatments of olive trees by-products on chemical composition, degradability, cell wall constituents, digestibility and nutritive value and its feeding effect on productive performance of growing sheep. Eighteen (½ Finnish Landrace × ½ Rahmani) lambs with average body weight 18.00±0.40 kg and 4 months old were used in this study for 120 days. Lambs were distributed into three similar groups (6 lambs each) and randomly assigned to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The finding is in agreement with Fouda (2008) who reported a lower feed costs per kg of weight gain and higher net profit per animal in lambs fed fungal treated diets compared to lambs fed untreated diet. Similarly, lower feed cost per kg gain and higher net revenue were reported by Mahrous et al. (2019) and Maharous et al.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The finding is in agreement with Fouda (2008) who reported a lower feed costs per kg of weight gain and higher net profit per animal in lambs fed fungal treated diets compared to lambs fed untreated diet. Similarly, lower feed cost per kg gain and higher net revenue were reported by Mahrous et al. (2019) and Maharous et al.…”
Section: Discussionmentioning
confidence: 58%
“…(2011) reported that treatment of rice straw (RS) and corn stalks (CS) with Trichoderma viride improve the digestibility of CP, CF, NDF, ADF, ADL and cellulose with a ration containing biologically treated by-products than untreated. Mahrous et al. (2019) stated that the digestibility of dry matter, organic matter, crude protein, nutreal detergent fiber and acid detergent fiber were significantly higher in sheep fed ration containing olive tree by-products treated with EM than untreated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Soest (2006) summarized the main deficiencies of RS that affect its value as a ruminant feed as being its high lignin content and conversion to silicates, delayed and limited degradation of carbohydrates, and low nitrogen content. According to Kholif et al (2005) and Mahrous (2005), roughages treated with fungi had higher TDN levels and DCP compared to untreated materials, and they also had better (P < 0.05) nutrient digestibility.…”
Section: Effect On Nutritive Valuementioning
confidence: 97%